A Note on Tenth Five Year Plan 2002-2007 Annual Plan 2002-03 - Planning Commission (Planning Commission, 2002)
The Approach to the Tenth Five Year Plan, as finalized by the National Development Council (N.D.C.) proposes to shift the focus, of planning from merely resources to policy and procedural and institutional changes which are considered essential for every Indian to realize his or her potential. In view of the continued importance of public action in the development process, there has to be emphasis on increasing the efficiency of public interventions. These measures collectively are expected to create an economic, political and social ambience in the country conducive to human development. The N.D.C. approved inter alia the following approach which is relevant to States
Government of Chhattisgarh Finance Planning, Economics & Statistics Department